#Sciencemustfall and Africanising the curriculum: findings from an online interaction. (September 2018) - Ally, Yaseen; August, Justin
Dialogue on the relevance of psychology in South Africa cannot be established if it excludes cultural belief systems and the implications they pose on the lived experiences of individuals. Dialogue on cultural beliefs, however, brings with it conflict between scientific thinking and cultural beliefs. In this article, 11, 124 online comments in response to a #sciencemustfall video during the #feesmustfall 2016 protests in South Africa were analysed using a thematic content analysis. The analysis focused on online comments posted in response to the story of a protesting student recommending that #sciencemustfall and that science must be built on the belief in witchcraft and the supernatural. The findings suggest that Africanising of curricula is associated with the perception that Western scientific thinking is absolute at the expense of cultural belief systems. There was also racist resistance to Africanising the curriculum.